Characterization of active paper packaging incorporated with ginger pulp oleoresin. Issue 1 (January 2016) - Wiastuti, T; Khasanah, L U; Kawiji, W Atmaka; Manuhara, G J; Utami, R
Abstract: Utilization of ginger pulp waste from herbal medicine and instant drinks industry in Indonesia currently used for fertilizer and fuel, whereas the ginger pulp still contains high oleoresin. Active paper packaging were developed incorporated with ginger pulp oleoresin (0%, 2%, 4%, and 6% w/w). Physical (thickness, tensile strength, and folding endurance, moisture content), sensory characteristics and antimicrobial activity of the active paper were evaluated. Selected active paper then were chemically characterized (functional groups). The additional of ginger pulp oleoresin levels are reduced tensile strength, folding endurance and sensory characteristic (color, texture and overall) and increased antimicrobial activity. Due to physical, sensory characteristic and antimicrobial activity, active paper with 2% ginger pulp oleoresin incorporation was selected. Characteristics of selected paper were 9.93% of water content; 0.81 mm of thickness; 0.54 N / mm of tensile strength; 0.30 of folding endurance; 8.43 mm inhibits the growth of Pseudomonas fluorescence and 27.86 mm inhibits the growth of Aspergillus niger (antimicrobial activity) and neutral preference response for sensory properties. For chemical characteristic, selected paper had OH functional group of ginger in 3422.83 cm -1 of wave number and indicated contain red ginger active compounds.